Demographic parameters and main biotic factors of two Dacini species, Bactrocera cucurbitae and Dacus ciliatus (Diptera, Tephritidae) in reunion Island - Vayssières, Jean-François; Carel, Y.; Coubes, M. (2004)
Réunion Island is characterized by a particular orography and a variable distribution of host plants for Dacini species. A complex of 3 Dacini species infests 16 host plant species belonging to the family Cucurbitaceae. These three species of vegetable fruit flies represent the primary pests of this plant family and are the main insect problem for cucurbit crops. We included in this study the two speciesB. cucurbitae (melon fly) and D. ciliatus (Ethiopian fruit fly). Adults of B. cucurbitae are classified as ‘R-strategists’, spending more energy than D. ciliatus in effectively using environmental resources. Adults ofD. ciliatus can be classified as ‘K-strategists’. B. cucurbitae is the species best adapted to exploit short-lived host plants. This adaptation explains its predominance over D. ciliatus under larval interspecific competition on Réunion Island.